Draft Fifth Five Year Plan 1974-79 Volume II - Planning Commission, Government of India (Planning Commission, Government of India, 1974)
One of the main objectives of the Fourth Plan, 77 in the agricultural sector, was to create conditions necessary for a sustained increase of about five per cent per annum over the next decade. More specifically, in respect of food grains, the Fourth Plan assumed a production level of 98 million tonnes in the base year and set a target of 129 million tonnes for the terminal year of the Plan.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Fifth Five Year Plan - India